2021
DOI: 10.1186/s13058-021-01472-1
|View full text |Cite
|
Sign up to set email alerts
|

Oestrogen deprivation induces chemokine production and immune cell recruitment in in vitro and in vivo models of oestrogen receptor-positive breast cancer

Abstract: Background Oestrogen receptor-positive (ER+) breast cancer is commonly treated using endocrine therapies such as aromatase inhibitors which block synthesis of oestradiol, but the influence of this therapy on the immune composition of breast tumours has not been fully explored. Previous findings suggest that tumour infiltrating lymphocytes and immune-related gene expression may be altered by treatment with aromatase inhibitors. However, whether these changes are a direct result of impacts on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 59 publications
1
4
0
Order By: Relevance
“…If specific immune cell populations are blocked, normal breast development is impacted 48 , 49 . Supporting our work with endocrine therapy and oophorectomy, estrogen deprived BCa cells with increased levels of chemokines compared to non-deprived cells, enhance immune cell migration 50 . Using qPCR on epithelial cells isolated from treated mammary glands we found that transcript for Csf2, Interferon-γ (Ifn-γ) and Ccl5 were increased by estrogen exposure.…”
Section: Discussionsupporting
confidence: 57%
“…If specific immune cell populations are blocked, normal breast development is impacted 48 , 49 . Supporting our work with endocrine therapy and oophorectomy, estrogen deprived BCa cells with increased levels of chemokines compared to non-deprived cells, enhance immune cell migration 50 . Using qPCR on epithelial cells isolated from treated mammary glands we found that transcript for Csf2, Interferon-γ (Ifn-γ) and Ccl5 were increased by estrogen exposure.…”
Section: Discussionsupporting
confidence: 57%
“…Persistent physical symptoms can increase fatigue and hinder patients' return to normal life, thereby reducing their quality of life. Therefore, continuous and systematic symptom management is necessary for breast cancer patients to adapt to normal life [30].…”
Section: Discussionmentioning
confidence: 99%
“…[71] Similar to other immune cells, CD4 + T-cells are attracted to TME of BC patients by chemokines secreted by the tumor: TNF-𝛼, CCL5, CCL18, CCL22, IL-6, IL-8, IL-13, etc. [46,90,91] BC patients are characterized by high levels of CCL18, which recruits Th0 to TME by binding to the membraneassociated phosphatidylinositol transfer protein 3 (PITPNM3) receptor on CD4 + T-cells. [90,92] On the other hand, Tregs recruitment to TME requires the secretion of CCL1, CCL2, CCL5, CCL28, CXCL12, IL-35, and CXCR4.…”
Section: Tumor-infiltrating Cd4 + T-cells In Breast Cancermentioning
confidence: 99%